The Effect Of Using Group Investigation (GI) Method On Students’ Writing Achievement Of Eleventh Grade Of SMA Swasta Pelita Bulu Cina - Dela Sapitri, Conny, Seget Tartiyoso (CV. PUSDIKRA MITRA JAYA, 2022)
The objective of the study is to find out whether Group Investigation Method (GIM) affect on Students’ Writing Achievement of Eleventh Grade of SMA Swasta Pelita Bulu Cina. The subject were the all tenth grade students’ with the population of 70 students. And 70 students were chosen as the ample each class consisted 35 students. This study was quasi experimental research. This study used control class and experimental class as design of research, which acts as a controlled class benchmark basic ability st udents’ on writing achievement without application of strategy, while the experimental class was given Group Investigation Method (GIM). The data collected from this study were analyzed using t -test formula. The result of this study that was a positive effect of the result students’ writing achievement after used Group Investigation Method (GIM). It can be seen from the data analysis, The data were collected by administering tests. Then, the data were analyzed by appying the pre test and the post test. The t-test formula both in experimental and control group (7.04) in which t-table is 2.000 (p=0.05), to was higher than tt in significant level 5%, so the alternative hypothesis (Ha) was accepted and the null hypothesis (H 0) was rejected. In order words, using Group Investigation Method (GIM) had effect on students’ writing achievement at the eleventh grade of SMA Swasta Pelita Bulu Cina.